2021
DOI: 10.3389/fmicb.2021.785737
|View full text |Cite
|
Sign up to set email alerts
|

The Succession of Bacterial Community Attached on Biodegradable Plastic Mulches During the Degradation in Soil

Abstract: Despite the increasing application of biodegradable plastic mulches (BDMs) in agriculture, the colonization and succession of the attached microbial community on BDMs during their degradation processes remain poorly characterized. Here, we buried four types of commonly used BDMs, including pure polylactic acid (PLA), pure polybutylene adipate terephthalate (PBAT), and two mixtures of PLA and PBAT (85:15 and 15:85 w/w), and one classic polyethylene (PE) mulch in soil for 5 months. Both plastic components and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…In our study we isolated microbial strains from the plastisphere of cold terrestrial environments belonging almost exclusively to the phyla Actinobacteria, Proteobacteria and Ascomycota. Especially the orders Burkholderiales, Pseudomonadales, and Streptomycetales and the genus Pseudogymnoascus were repeatedly isolated, which agrees with previous reports of the soil plastisphere microbiome analyzed by culture-independent genomic methods ( Rüthi et al, 2020 , 2023 ; Ju et al, 2021 ; Sun et al, 2022 ; Zhang et al, 2022 ) and microbial cultivation ( Cosgrove et al, 2007 ). Further, these phyla (+ Firmicutes) are the principal taxa known to be involved in the degradation of PUR, PBAT and PLA ( Cregut et al, 2013 ; Gambarini et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study we isolated microbial strains from the plastisphere of cold terrestrial environments belonging almost exclusively to the phyla Actinobacteria, Proteobacteria and Ascomycota. Especially the orders Burkholderiales, Pseudomonadales, and Streptomycetales and the genus Pseudogymnoascus were repeatedly isolated, which agrees with previous reports of the soil plastisphere microbiome analyzed by culture-independent genomic methods ( Rüthi et al, 2020 , 2023 ; Ju et al, 2021 ; Sun et al, 2022 ; Zhang et al, 2022 ) and microbial cultivation ( Cosgrove et al, 2007 ). Further, these phyla (+ Firmicutes) are the principal taxa known to be involved in the degradation of PUR, PBAT and PLA ( Cregut et al, 2013 ; Gambarini et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, studies about plastisphere in soil also demonstrated the dominant roles of stochastic processes in shaping the plastisphere microbiota. For instance, Ju et al have found a higher proportion of stochastic processes than deterministic processes for plastisphere ( 45 ). In the current study, the NST values indicated that the stochastic processes dominantly contributed to the plastisphere communities.…”
Section: Resultsmentioning
confidence: 99%
“…The soil genomic DNA was extracted by the PowerSoil DNA Isolation Kit (Qiagen, Germany) following the manufacturer’s instructions. The extracted DNA was amplified by the 16S rRNA universal primer set, 515 forward (5’-GTGCCAGCMGCCGCGGTAA-3′) and 806 reverse (5-'GGACTACHVGGGTWTCTAAT-3′) that targeted the V4 hypervariable regions of the prokaryotic 16S rRNA genes ( Yarza et al, 2014 ; Ju et al, 2021 ). The ITS2 region of fungal ribosomal encoding genes was amplified with the primers gITS7 (5’-GTGARTCATCGARTCTTTG-3′) and ITS4 (5’-TCCTCCGCTTATTGATATGC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we constructed an RF model to identify the most distinguished taxa from inside and outside of coking plant samples and test the accuracy of the biomarkers. Significantly enriched or depleted ASVs of bacteria and fungi were designated as biomarkers and the RF package v.4.6–14 was used with default parameters ( Zhang et al, 2019 ; Ju et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%